2021
DOI: 10.3390/plants11010059
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Physiological Response of Durum Wheat Grain to Short-Term Heat Stress during Early Grain Filling

Abstract: In a changing climate, extreme weather events such as heatwaves will be more frequent and could affect grain weight and the quality of crops such as wheat, one of the most significant crops in terms of global food security. In this work, we characterized the response of Triticum turgidum L. spp. durum wheat to short-term heat stress (HS) treatment at transcriptomic and physiological levels during early grain filling in glasshouse experiments. We found a significant reduction in grain weight (23.9%) and grain d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 97 publications
1
14
0
Order By: Relevance
“…In addition, an analysis of flag leaves of plants exposed to high temperature displayed an up-regulation of the expression for the ribulose-1,5-bisphosphate carboxylase oxygenase (Rubisco) large subunit and for Rubisco activase genes, while a down-regulation of genes involved in light reactions, carbohydrate metabolism, glycolysis, mitochondrial electron transport, nitrogen (N) metabolism, amino acid metabolism, cell modification and secondary metabolism was observed [ 32 ]. In grains at the early filling stage, short-term heat stress produced an initial transcriptomic response characterized by the induction of chaperones and genes associated with photosynthesis and the inhibition of genes involved in carbohydrate metabolism [ 25 ]. Moreover, the molecular response to drought can be influenced in durum wheat plants with alteration in pigment content by genes encoding antioxidant enzymes, photosystem components, and enzymes representing carbohydrate metabolism and the tricarboxylic acid cycle [ 17 ].…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…In addition, an analysis of flag leaves of plants exposed to high temperature displayed an up-regulation of the expression for the ribulose-1,5-bisphosphate carboxylase oxygenase (Rubisco) large subunit and for Rubisco activase genes, while a down-regulation of genes involved in light reactions, carbohydrate metabolism, glycolysis, mitochondrial electron transport, nitrogen (N) metabolism, amino acid metabolism, cell modification and secondary metabolism was observed [ 32 ]. In grains at the early filling stage, short-term heat stress produced an initial transcriptomic response characterized by the induction of chaperones and genes associated with photosynthesis and the inhibition of genes involved in carbohydrate metabolism [ 25 ]. Moreover, the molecular response to drought can be influenced in durum wheat plants with alteration in pigment content by genes encoding antioxidant enzymes, photosystem components, and enzymes representing carbohydrate metabolism and the tricarboxylic acid cycle [ 17 ].…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…RT qPCR, micro array, and next generation sequencing, is known as transcriptomics [ 213 ]. Recently, Arenas-M et al [ 214 ] identified the role of novel TFs, e.g., members of the DOF family, that impart better grain quality via regulating glycogen and starch biosynthetic processes in grains under short term heat stress. This helps in discovering underlying molecular and physiological mechanisms of plant response to different abiotic stresses.…”
Section: Adaptation Strategiesmentioning
confidence: 99%
“…The temperature anomaly distribution, on the other hand, is shifting toward higher temperatures [ 7 ], and wheat production is estimated to be reduced by up to 6% for each 1°C rise in temperature. Arenas-M et al [ 8 ] have reported a significant reduction in grain weight (23.9%) and grain dimensions due to heat-stress in wheat. In comparison to the control condition, grain quality was also significantly impacted, with a fall in starch content (20.8%) and an increase in grain protein levels (14.6%) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%